IMPROVING THE MATHEMATICS LEARNING PROCESS AND OUTCOMES USING THE NHT MODEL BASED ON UNO CARD MEDIA IN CLASS V OF SDN 81/II MUARA BUNGO - azka ulhaq shetarro; Randi Eka Putra; Elvima Nofrianni (Prima: Jurnal Pendidikan Matematika, 2026)
This research is motivated by the low mathematics learning process and outcomes at SDN 81/II Muara Bungo due to the dominance of conventional learning and limited media. This Classroom Action Research (CAR) aims to improve the quality of learning through the Numbered Heads Together (NHT) cooperative model based on UNO cards. Implemented in two cycles with the stages of planning, action, observation, and reflection, the study involved 28 fifth grade students. The results show that the integration of UNO cards in the NHT syntax creates a positive interactive and competitive learning atmosphere. A significant increase is seen from the classical completion rate which increased from 57% in Cycle I to 86% in Cycle II, exceeding the target indicator of 80%. It is concluded that the UNO card-based NHT model is effective in improving the mathematics learning process and outcomes.